Investigation of the mechanisms of sonodynamic therapy - Singh, K (2024)
There is a pressing need to develop novel platform cancer therapeutics that are efficient, reduce side effects, and are minimally invasive. One emerging platform is photodynamic therapy where light is used as an external stimulus to activate drugs at a target location, however, clinical applications are limited due to poor light penetration. Previously, it has been shown that ultrasound with and without cavitation nuclei can be used to activate photodynamic drugs (sonodynamic therapy – SDT), however, the mechanism of this activation remains unclear. A proposed mechanism for SDT is that light produced by cavitation can activate photodynamic drugs at the target location resulting in reactive oxygen species (ROS) production (which leads to cell death). However, through temporal uncoupling of ultrasound application and compound administration in vitro, testing of ultrasound plus microbubble-only related cell death, and developing positive controls for cell permeabilization (sonoporation), this work shows that the mechanical effects of cavitation plays an important role in SDT-induced cell death in vitro and potentially explains the high levels of cell death observed when comparatively low concentrations of ROS are generated. This work also proposes a set of standard controls for SDT mechanistic studies.